THE ROLE OF TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE IN INCREASING EMPLOYEE COMMITMENT - Teguh Setiawan Wibowo; Didi Suhendi; I Made Adi Suwandana; Tanti Widia Nurdiani; Fatimah Malini Lubis (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research is motivated by the importance of employee commitment in achieving company goals. This study aims to determine and analyze the influence of transformational leadership and organizational culture on employee commitmentThe research method used in this study is a descriptive method with a quantitative approach. The sample for this study consisted of 100 employees using a random sampling method. Data is collected via surveys distributed via google forms. The instruments used have been tested for validity and reliability. Collected data were analyzed using the classical assumption test and multiple linear regression using excel and SPSS. This is shown by the results of this study 1) transformational leadership has a positive and significant effect on employee commitment, 2) organizational culture has a positive and significant effect on employee commitment, and 3) transformational leadership and organizational culture have a positive and significant effect on employee commitment. The findings of this study suggest that if companies want to increase employee commitment, companies must improve transformational leadership and organizational culture.